2020
DOI: 10.3390/en13030702
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Solar Radiation Transposition Models for Passive Energy Management and Building Integrated Photovoltaics

Abstract: Incident solar radiation modelling has become of vital importance not only in architectural design considerations, but also in the estimation of the energy production of photovoltaic systems. This is particularly true in the case of buildings with integrated photovoltaics (PV) systems having a wide range of orientations and inclinations defined by the skin of the building. Since solar radiation data at the plane of interest is hardly ever available, this study presents the analysis of two of the most represent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 49 publications
0
14
0
Order By: Relevance
“…where b  is the atmosphere transmittance, due to the influence of the scattering and absorption of atmosphere, the direct solar radiation reaching the earth's surface has some attenuation. The atmosphere transmittance for the direct solar radiation proposed by Kretith and Kreider in clear sky can be given by [7]:…”
Section: Solar Radiation Modelmentioning
confidence: 99%
“…where b  is the atmosphere transmittance, due to the influence of the scattering and absorption of atmosphere, the direct solar radiation reaching the earth's surface has some attenuation. The atmosphere transmittance for the direct solar radiation proposed by Kretith and Kreider in clear sky can be given by [7]:…”
Section: Solar Radiation Modelmentioning
confidence: 99%
“…Their results indicated that it is possible to achieve high annual rates of electricity demand in many municipalities, reaching even more than 100% in some cases. Toledo et al [156] evaluated the most representative transposition models for building integrated photovoltaics and passive energy management. Their study revealed that PV façades have an essential impact on solar energy potential.…”
Section: Estimating Solar Radiation Using Gismentioning
confidence: 99%
“…The separation of the individual irradiance parts is necessary because the diffuse irradiance component is very complex to model. A comprehensive discussion on models can be found in [23] and a comparison and rating of different models in [24,25]. Figure 4 shows a simplified model structure to calculate the in-plane irradiance [26].…”
Section: In-plane Irradiance Imputationmentioning
confidence: 99%